PELATIHAN MANAJEMEN UNTUK PENINGKATAN PRODUKTIVITAS DAN KEBERLANJUTAN KETAHANAN PANGAN(SINDANG SARI IV RT 02 RW 05 KEL. SUKAMULYA KEC. CINAMBO KOTA BANDUNG) - Adrie Charviandi; Yusnaini, Yesi Suhartini, Rizka Noristaman, Deasy Sandya, Nenden Hendayani (Adiba Aisha Amira, 2023)
Food security is a strategic issue with a significant impact on economic stability and community welfare, especially in densely populated urban areas. In Indonesia, urbanization and changes in consumption patterns increase the need for safe, quality and affordable food. However, limited urban space hinders local food production, so urban agriculture is a potential solution to support food security in urban areas. Sukamulya Village, especially Sindang Sari IV RT 02 RW 05, Cinambo District, Bandung City, faces food security challenges with high population density and limited land. Innovative approaches are needed to increase local food production, one of which is through urban agricultural management training that focuses on increasing productivity and sustainability. This training aims to not only increase crop yields, but also encourage sustainable and environmentally friendly agricultural practices. Using appropriate management techniques, efficient land use, and processing organic waste into natural fertilizer are some of the strategies implemented. Apart from that, this training improves farming business management skills so that residents can manage agricultural products more effectively and increase family income. This service evaluates the impact of urban agricultural management training on productivity and sustainability of food security in Sindang Sari IV, involving RT women as the main participants. The results are expected to provide an overview of the effectiveness of the training and recommendations for developing similar programs in other urban areas, increasing local food security and empowering communities to be independent and sustainable in meeting their food needs.